Religion and society - on the present-day religious situation - Udeani, Chibueze.; Reiterer, Friedrich.; Zapotoczky, Klaus.; Kunstmann-Hirnböck, Alexandra. (Intercultural Theology and Study of Religions, 2014)
Religion is today mainly present in the consciousness of people through keywords like fundamentalism, global conflict or violence. But as what is religion understood and how does it affect the society are questions that need to be examined separately. The contributions in this volume will examine the sub-questions that pose themselves in this light: 1) What influence does religion exercise on our social life forms? 2) What are the religious societal prerequisites? And how is visible religion affected by these? 3) How do these questions present themselves both externally and internally in the contemporary perception?